Roman Jakobson a počátky pražského lingvistického kroužku (ke kořenům strukturální estetiky) - Zelenka, Miloš (Slavia Occidentalis, 2014)
Relying on hitherto unpublished archive materials, this paper deals with the life and works of R. Jakobson in inter-war Czechoslovakia, with special emphasis on the methodological transformation of Russian formalism and Czech structuralism. Conjointly, it reconstructs the theoretical sources of Jakobson’s structural aesthetics (such as Russian formalism; Husserl’s phenomenology; anti-psychological concepts; the „Neo-Kantian” School; the Czech tradition of formism as represented namely by O. Hostinský; Masaryk’s views on linguistic structure; etc.), as they are reflected in his preoccupation with poetic language and in producing a metrical theory based on the analysis of three basic elements of Czech metrics (quantity, stress and caesura). The Russian exile Jakobson also helped to establish the Linguistic Circle of Prague by analogy with the Russian model. At the turn of 1930s, Jakobson broadened the focus of his research, which then encompassed, along with linguistics and metrics, also Medieval Czech literature, and Slavonic cultural and comparative studies, where literary history was conceived as immanent movement of poetical forms determined by the capacity if inter-subjective structure and intents of the creative individual. Jakobson’s commending the dialogic nature of scholarly research notwithstanding, his works had epitomised modern rationalism and completed scientistic ideas even before the era ended.